Novel high-mechanical-strength and high-toughness conductive polymer, preparation method thereof and application of novel high-mechanical-strength and high-toughness conductive polymer as carbon-based composite bipolar plate binder

By introducing carboxy and hydroxyl groups into polyionic liquid materials and using photo-induced polymer or RAFT polymerization to prepare high mechanical strength conductive polymers as binders, the coordination problem between the conductivity and bending strength of the bipolar plate is solved, and the problem of improvement of the Performance of carbon-based composite bipolar plates.

CN119143920APending Publication Date: 2024-12-17LIAONING UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411259762.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Traditional bipolar plates face the problem of mutual constraints on bending strength and conductivity, and the resin layer formed on the surface will weaken the conductivity of the bipolar plate. How to improve the mechanical strength of polyion liquid materials, realize their mechanical strength, adhesion and conductivity. Coordination is a research hotspot.

Method used

By introducing carboxy and hydroxyl groups into the monomer structure, using photo-induced polymerization or RAFT polymerization, regulating the monomer ratio or addition order, a new type of conductive polymer with high mechanical strength and high toughness is prepared and used as a binder to be different from the different Carbon-based composite bipolar plates are prepared by carbon material composite molding.

Benefits of technology

It achieves high mechanical strength, excellent adhesion performance and good conductivity, improves the plane conductivity and bending strength of the carbon-based composite bipolar plate, and improves thermal stability and corrosion current performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143920A_ABST
    Figure CN119143920A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of conductive polymer synthesis, and particularly relates to a novel conductive polymer with high mechanical strength and high toughness, a preparation method of the conductive polymer and application of the conductive polymer as a carbon-based composite bipolar plate binder. The conductive polymer is based on the combined action of multiple supramolecular acting forces, the structure is novel, the structural composition and the synthesis formula are uniquely designed, and the preparation method comprises the following steps: preparing a series of carboxyl functionalized imidazole ionic liquid monomers with different carbon chain lengths and different anion types by utilizing a photo-initiation polymerization method or an RAFT polymerization method; a series of conductive polymers with high mechanical strength and high toughness are constructed by regulating and controlling the proportion of imidazolium ionic liquid monomers and hydroxyl functionalized acrylate monomers and the adding sequence of the monomers, and the conductive polymers are used as a binder to be compounded with different carbon materials to manufacture the composite bipolar plate. The method is simple, easy to operate and low in cost, has universality, can perform targeted design on the microstructure and function of the material according to different requirements, and is wide in application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of conductive polymer synthesis, and in particular relates to a novel conductive polymer with high mechanical strength and high toughness, a preparation method thereof, and an application thereof as a binder for carbon-based composite bipolar plates. Background Art

[0002] With the development of the world economy, people's demand for energy is increasing. At present, the energy consumption structure is still dominated by fossil fuels, but its reserves are limited, and the toxic and harmful gases produced have brought serious environmental problems and posed a serious threat to life. Therefore, the development of new energy and renewable energy is imminent. New energy and renewable energy, mainly solar energy and wind energy, are unstable, discontinuous and difficult to dispatch, so large-scale energy storage technology is needed as a technical cornerstone. Compared with other energy storage technologies, all-vanadium liquid flow batteries have the advantages of large storage capacity, long service life, safety and reliability, and have become one of the most promising large-scale megawatt-class energy storage technologies.

[0003] Bipolar plates are key components of battery stacks composed of single cells connected in series. They are required to have not only high electrical conductivity, thermal conductivity, corrosion resistance, low density, high mechanical strength and gas permeability resistance, but also low material cost, easy processing, and good dimensional stability. Among various bipolar plate materials, composite bipolar plates with carbon materials as conductive aggregates and resins as binders basically maintain the electrical conductivity, corrosion resistance and processability of carbon materials and polymers. At the same time, the combination of tough and soft resin materials and solid and hard carbon materials promotes each other, exerting a synergistic effect of "1+1>2", which improves the strength of bipolar plates. However, traditional bipolar plates face the problem of mutual constraints between bending strength and electrical conductivity, and the problem that the resin layer formed on the surface will weaken the electrical conductivity of the bipolar plate. Therefore, the development of binders with high mechanical strength, high toughness and electrical conductivity has become one of the key technologies for the development of bipolar plates.

[0004] Polyionic liquids are a new type of ionic polymers with anionic and cationic structures in the main chain. They not only retain the excellent properties of ionic liquids such as non-flammability, good thermal stability, wide electrochemical window and high ionic conductivity, but also have the advantages of easy processing and adjustable structure of polymers. They are widely used in electrochemistry, new energy, materials, polymers and emerging cross-fields, especially batteries. Using polyionic liquid-based conductive materials as binders and compounding them with different carbon materials to prepare carbon-based composite bipolar plates has great application market and potential value. However, how to improve the mechanical strength of polyionic liquid materials and achieve the coordination of their mechanical strength, adhesion properties and conductivity has always been a research hotspot in the field of materials.

[0005] In order to improve the mechanical strength of polyionic liquid materials, researchers have done a lot of work on the segment structure and aggregate structure of polyionic liquids, such as regulating the anion and cation configurations, introducing other chemical or physical synergistic effects, etc. The main innovation of the present invention is that carboxyl and hydroxyl groups are introduced into the monomer structure through molecular structure design, photoinitiated polymerization or RAFT polymerization is used, the monomer ratio or addition order is regulated, and a series of new conductive polymer materials with high mechanical strength and high toughness are prepared, and they are used as binders to prepare carbon-based composite bipolar plates with different carbon materials, opening up a new way to develop high-performance polyionic liquid-based binder materials. Summary of the invention

[0006] To achieve the above objectives, the present invention prepares a new type of conductive polymer with high mechanical strength and high toughness and uses it as a binder in a carbon-based composite bipolar plate.

[0007] The technical solution adopted by the present invention is:

[0008] The novel conductive polymer with high mechanical strength and high toughness is a polyionic liquid-based cross-linked network conductive copolymer obtained by copolymerizing carboxyl-functionalized imidazole ionic liquid monomers with hydroxyl-functionalized acrylate monomers.

[0009] Furthermore, in the above-mentioned novel conductive polymer with high mechanical strength and high toughness, the chemical structure formula of the carboxyl functionalized imidazole ionic liquid monomer is as shown in (I):

[0010]

[0011] Among them, X1 - For TFSI - 、SbF6 - CF3SO3 - CF3COO - 、FSI - 、N(C2F5SO2)2 - 、CH3SO3 - Any one of the following; n represents the carbon chain length of the ionic liquid monomer, and its value ranges from 1 to 10.

[0012] Furthermore, in the above-mentioned novel conductive polymer with high mechanical strength and high toughness, the chemical structure of the hydroxyl functionalized acrylate monomer is any one of (II), (III) and (IV):

[0013]

[0014] The preparation method of the novel high mechanical strength and high toughness conductive polymer is as follows: using photoinitiated polymerization, carboxyl functionalized imidazole ionic liquid monomers and hydroxyl functionalized acrylate monomers are copolymerized to construct a random structured polyionic liquid-based cross-linked network conductive copolymer.

[0015] Furthermore, in the above-mentioned preparation method, the specific steps of the photoinitiated polymerization method are as follows: carboxyl functionalized imidazole ionic liquid monomer and hydroxyl functionalized acrylate monomer are mixed evenly with 1-hydroxycyclohexyl phenyl ketone (184) with a total mass fraction of 1% of the two monomers as a photoinitiator, and placed in a 38×8×1mm glass mold, and irradiated under a wavelength of 365nm ultraviolet lamp for 0.5 to 20min for polymerization. After the polymerization is completed, a random structured polyionic liquid-based cross-linked network conductive copolymer is obtained.

[0016] Preferably, the molar ratio of the carboxyl-functionalized imidazole ionic liquid monomer to the hydroxyl-functionalized acrylate monomer is 1:100 to 100:1.

[0017] The second preparation method of the above-mentioned new type of high mechanical strength and high toughness conductive polymer is as follows: using reversible addition-fragmentation chain transfer polymerization (RAFT), carboxyl functionalized imidazole ionic liquid monomers and hydroxyl functionalized acrylate monomers are copolymerized in the presence of AIBN and RAFT agents, and by regulating the order of monomer addition, a block structure or random structure polyionic liquid-based cross-linked network conductive copolymer is constructed.

[0018] Furthermore, in the above-mentioned preparation method, the chemical structure of the RAFT agent is any one of (V), (VI), (VII), (VIII), (IX), and (X):

[0019]

[0020] Furthermore, in the above-mentioned preparation method, the specific steps of the reversible addition-fragmentation chain transfer polymerization method are as follows: under a nitrogen atmosphere, the carboxyl functionalized imidazole ionic liquid monomer and the hydroxyl functionalized acrylate monomer dissolved in toluene are evenly mixed to obtain a monomer mixed solution; a RAFT agent with a total mass fraction of 0.5% of the two monomers and an AIBN with a total mass fraction of 1% of the two monomers are dissolved in toluene, and the obtained mixed solution is added to the above-mentioned monomer mixed solution, and polymerized at 70°C for 12 to 24 hours. After the polymerization is completed, it is purified and dried to obtain a random-structured polyionic liquid-based cross-linked network conductive copolymer.

[0021] Furthermore, in the above-mentioned preparation method, the specific steps of the reversible addition-fragmentation chain transfer polymerization method are as follows: under a nitrogen atmosphere, dissolving a carboxyl-functionalized imidazole ionic liquid monomer in toluene to obtain a monomer solution; dissolving a RAFT agent having a total mass fraction of 0.5% of the two monomers and an AIBN having a total mass fraction of 1% of the two monomers in toluene, and adding the obtained mixed solution to the above-mentioned monomer solution, polymerizing at 70°C for 12 to 24 hours, and then adding a hydroxyl-functionalized acrylate monomer, continuing to polymerize for 12 to 24 hours, purifying and drying after the polymerization, and obtaining a block-structured polyionic liquid-based cross-linked network conductive copolymer.

[0022] Preferably, the molar ratio of the carboxyl-functionalized imidazole ionic liquid monomer to the hydroxyl-functionalized acrylate monomer is 1:100 to 100:1.

[0023] The above-mentioned new type of high mechanical strength and high toughness conductive polymer is used as a binder in carbon-based composite bipolar plates.

[0024] Furthermore, the above-mentioned application method is as follows: the conductive skeleton material and the new type of high mechanical strength and high toughness conductive polymer as a binder are placed in a mortar and mixed to obtain a uniform mixture, the above mixture is placed on a flexible graphite paper, and placed in a hot press for hot pressing at a pressure of 3MPa and a temperature of 150°C, and then the heater is turned off and maintained at a pressure of 3MPa to cool to room temperature, and the pressure is removed to obtain a carbon-based composite bipolar plate.

[0025] Furthermore, the thickness of the carbon-based composite bipolar plate is 0.8 to 1.2 mm.

[0026] Furthermore, in the above application, the content of the conductive skeleton material in the carbon-based composite bipolar plate is 15wt.% to 30wt.%.

[0027] Furthermore, in the above application, the preparation method of the conductive skeleton material is as follows: the conductive material is placed in a beaker, manually stirred with a glass rod for 10 minutes, then transferred to a mortar, and manually ground for 10 minutes to prepare the conductive skeleton material.

[0028] Preferably, the conductive material is any one of graphite (expanded graphite, flake graphite), graphene, carbon fiber, carbon nanotubes, or a mixture of two thereof.

[0029] The beneficial effects of the present invention are:

[0030] 1. The present invention provides a novel polyionic liquid-based conductive polymer material with high mechanical strength and high toughness. In the material, carboxyl groups and hydroxyl groups are introduced into the polymer chain to provide active sites for the introduction of hydrogen bonds and ion-dipole interactions. At the same time, the strength of the electrostatic interaction is further regulated by regulating the structure of anions and cations in the ionic liquid monomers, thereby providing a theoretical basis and experimental reference for the preparation of a cross-linked polyionic liquid-based conductive polymer material with adjustable performance.

[0031] 2. The present invention provides a method for preparing a novel polyionic liquid-based conductive polymer material. A series of conductive polymer materials with controllable microstructure (random or block), molecular weight and molecular weight distribution are prepared by photoinitiated polymerization (one-step method) or RAFT copolymerization (one-pot method). The method is simple, easy to operate, low-cost and universal, and has clear guiding significance for the preparation of polyionic liquid-based conductive polymer materials with precisely controllable structures.

[0032] 3. The present invention provides a new type of polyionic liquid-based conductive polymer material with high mechanical strength and high toughness. The material has high mechanical strength (5MPa) and toughness (elongation at break can reach 1900%), excellent adhesion properties and good conductivity, excellent bending strength (changeable shape), and good thermal stability (the temperature at weight decomposition of 5% can reach 370°C).

[0033] 4. The present invention provides a novel polyionic liquid-based conductive polymer material with high mechanical strength and high toughness. The material is composited with different carbon materials to prepare a series of carbon-based composite bipolar plate materials with different properties. The planar conductivity of the bipolar plate material is significantly improved (the planar conductivity is 130-160S cm -1 ), the bending strength can reach 80MPa, and the corrosion current is less than 28μA cm -2 . BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 These are characterization graphs of the bending and tensile properties of the polyionic liquid-based cross-linked network conductive polymers prepared in Examples 1-4, a to d are characterization graphs of the bending properties of the conductive polymers in Examples 1 to 4, respectively, and e is a characterization graph of the tensile properties of the conductive polymer in Example 4.

[0035] Figure 2 This is a characterization diagram of the adhesion performance of the polyionic liquid-based cross-linked network conductive copolymer prepared in Example 4.

[0036] Figure 3 This is a characterization diagram of the self-healing performance of the polyionic liquid-based cross-linked network conductive copolymer prepared in Example 4.

[0037] Figure 4It is a schematic structural diagram of the polyionic liquid-based cross-linked network conductive copolymer of the present invention. DETAILED DESCRIPTION

[0038] In order to further understand the present invention, the preferred experimental scheme of the present invention is described below in conjunction with embodiments, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention rather than limiting the claims of the present invention.

[0039] Example 1 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0040] Taking the conductive polymer having a molar ratio of 1-vinyl-3-carboxymethyl imidazolium bis(trifluoromethanesulfonyl)imide salt ionic liquid monomer ([VCMIm][TFSI]) to 2-hydroxyethyl acrylate monomer (HEA) as an example, the preparation method is as follows:

[0041] The anhydrous ethanol solution of [VCMIm][TFSI] monomer (2.6165 g, 6 mmol), HEA monomer (1.3934 g, 12 mmol), and 0.0401 g of 1-hydroxycyclohexyl phenyl ketone (184) photoinitiator was mixed evenly and stirred at room temperature for 5 min to obtain a precursor solution. The precursor solution was purged with argon gas, and then placed in a vacuum oven at 60°C and dried for 30 min to remove the ethanol solvent. A release agent was sprayed on the surface of a glass mold with a size of 38×8×1 mm. After the release agent was dried, the above-mentioned precursor solution was quickly injected into the mold and photocrosslinked and polymerized under 15W, 365nm wavelength ultraviolet light for 2 min (the distance between the ultraviolet lamp and the mold was fixed at 3 cm) to obtain a random structure polyionic liquid-based crosslinked network conductive copolymer.

[0042] Example 2 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0043] The method is the same as that of Example 1, except that the molar ratio of [VCMIm][TFSI] monomer to HEA monomer is replaced with 1:10, and the mass of 1-hydroxycyclohexyl phenyl ketone (184) photoinitiator is adjusted to 1% of the total mass fraction of the two monomers.

[0044] Example 3 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0045] The method is the same as that of Example 1, except that the molar ratio of [VCMIm][TFSI] monomer to HEA monomer is replaced with 1:50, and the mass of 1-hydroxycyclohexyl phenyl ketone (184) photoinitiator is adjusted to 1% of the total mass fraction of the two monomers.

[0046] Example 4 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0047] The method is the same as that of Example 1, except that the molar ratio of [VCMIm][TFSI] monomer to HEA monomer is replaced with 1:100, and the mass of 1-hydroxycyclohexyl phenyl ketone (184) photoinitiator is adjusted according to 1% of the total mass fraction of the two monomers.

[0048] Example 5 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0049] Taking the conductive polymer having a molar ratio of 1-vinyl-3-carboxymethylimidazole bis(trifluoromethanesulfonyl)imide salt ionic liquid monomer ([VCMIm][TFSI]) to 2-hydroxypropyl acrylate monomer (HPA) as an example, the preparation method is as follows:

[0050] The anhydrous ethanol solution of [VCMIm][TFSI] monomer (2.6165 g, 6 mmol), HPA monomer (1.5617 g, 12 mmol), and 0.0418 g of 1-hydroxycyclohexyl phenyl ketone (184) photoinitiator was mixed evenly and stirred at room temperature for 5 min to obtain a precursor solution. The precursor solution was purged with argon gas, and then placed in a vacuum oven at 60°C and dried for 30 min to remove the ethanol solvent. A release agent was sprayed on the surface of a glass mold with a size of 38×8×1 mm. After the release agent was dried, the above-mentioned precursor solution was quickly injected into the mold and photocrosslinked and polymerized under 15W, 365nm wavelength ultraviolet light for 2 min (the distance between the ultraviolet lamp and the mold was fixed at 3 cm) to obtain a random structure polyionic liquid-based crosslinked network conductive copolymer.

[0051] Example 6 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0052] The method is the same as that of Example 5, except that the molar ratio of [VCMIm][TFSI] monomer to HPA monomer is replaced with 1:10, and the mass of 1-hydroxycyclohexyl phenyl ketone (184) photoinitiator is adjusted to 1% of the total mass fraction of the two monomers.

[0053] Example 7 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0054] The method is the same as that of Example 5, except that the molar ratio of [VCMIm][TFSI] monomer to HPA monomer is replaced with 1:50, and the mass of 1-hydroxycyclohexyl phenyl ketone (184) photoinitiator is adjusted to 1% of the total mass fraction of the two monomers.

[0055] Example 8 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0056] The method is the same as that of Example 5, except that the molar ratio of [VCMIm][TFSI] monomer to HPA monomer is replaced with 1:100, and the mass of 1-hydroxycyclohexyl phenyl ketone (184) photoinitiator is adjusted to 1% of the total mass fraction of the two monomers.

[0057] Example 9 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0058] Taking the conductive polymer having a molar ratio of 1-vinyl-3-carboxymethyl imidazolium bis(trifluoromethanesulfonyl)imide salt ionic liquid monomer ([VCMIm][TFSI]) to 4-hydroxybutyl acrylate monomer (HBA) as an example, the preparation method is as follows:

[0059] The anhydrous ethanol solution of [VCMIm][TFSI] monomer (2.6165 g, 6 mmol), HBA monomer (1.7300 g, 12 mmol), and 0.0435 g of 1-hydroxycyclohexyl phenyl ketone (184) photoinitiator was mixed evenly and stirred at room temperature for 5 min to obtain a precursor solution. The precursor solution was purged with argon gas, and then placed in a vacuum oven at 60°C and dried for 30 min to remove the ethanol solvent. A release agent was sprayed on the surface of a glass mold with a size of 38×8×1 mm. After the release agent was dried, the above-mentioned precursor solution was quickly injected into the mold and photocrosslinked and polymerized under 15W, 365nm wavelength ultraviolet light for 2 min (the distance between the ultraviolet lamp and the mold was fixed at 3 cm) to obtain a random structure polyionic liquid-based crosslinked network conductive copolymer.

[0060] Example 10 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0061] The method is the same as that of Example 9, except that the molar ratio of [VCMIm][TFSI] monomer to HBA monomer is replaced with 1:10, and the mass of 1-hydroxycyclohexyl phenyl ketone (184) photoinitiator is adjusted to 1% of the total mass fraction of the two monomers.

[0062] Example 11 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0063] The method is the same as that of Example 9, except that the molar ratio of [VCMIm][TFSI] monomer to HBA monomer is replaced with 1:50, and the mass of 1-hydroxycyclohexyl phenyl ketone (184) photoinitiator is adjusted to 1% of the total mass fraction of the two monomers.

[0064] Example 12 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0065] The method is the same as that of Example 9, except that the molar ratio of [VCMIm][TFSI] monomer to HBA monomer is replaced with 1:100, and the mass of 1-hydroxycyclohexyl phenyl ketone (184) photoinitiator is adjusted to 1% of the total mass fraction of the two monomers.

[0066] Example 13 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0067] Taking the molar ratio of 1-vinyl-3-carboxymethylimidazolium bis(trifluoromethanesulfonyl)imide salt ionic liquid monomer ([VCMIm][TFSI]) to 2-hydroxyethyl acrylate monomer (HEA) as 1:2, the preparation of a random structure conductive polymer by RAFT copolymerization is as follows:

[0068] Under a nitrogen atmosphere, [VCMIm][TFSI] monomer (2.6165 g, 6 mmol) and HEA monomer (1.3934 g, 12 mmol) were dissolved in 10 mL of toluene at room temperature, and stirred for 10 min to mix evenly to obtain a monomer mixed solution; a mixed solution of BSTP (0.5% of the total mass fraction of the two monomers) and AIBN (1% of the total mass fraction of the two monomers) dissolved in 5 mL of toluene was added to the above monomer mixed solution, and polymerized at 70° C. for 12 to 24 h. After the polymerization, the mixture was purified and dried to obtain a polyionic liquid-based cross-linked network conductive copolymer with a random structure.

[0069] Example 14 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0070] The method is the same as Example 13, except that the molar ratio of [VCMIm][TFSI] monomer to HEA monomer is replaced with 1:10, and the amounts of BSTP and AIBN are adjusted accordingly.

[0071] Example 15 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0072] The method is the same as Example 13, except that the molar ratio of [VCMIm][TFSI] monomer to HEA monomer is replaced with 1:50, and the amounts of BSTP and AIBN are adjusted accordingly.

[0073] Example 16 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0074] The method is the same as Example 13, except that the molar ratio of [VCMIm][TFSI] monomer to HEA monomer is replaced with 1:100, and the amounts of BSTP and AIBN are adjusted accordingly.

[0075] Example 17 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0076] The method is the same as Example 13, except that the HEA monomer is replaced by the HPA monomer, and the amounts of BSTP and AIBN are adjusted accordingly.

[0077] Example 18 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0078] The method is the same as Example 14, except that the HEA monomer is replaced by the HPA monomer, and the amounts of BSTP and AIBN are adjusted accordingly.

[0079] Example 19 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0080] The method is the same as Example 15, except that the HEA monomer is replaced by the HPA monomer, and the amounts of BSTP and AIBN are adjusted accordingly.

[0081] Example 20 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0082] Taking the molar ratio of 1-vinyl-3-carboxymethyl imidazolium bis(trifluoromethanesulfonyl)imide salt ionic liquid monomer ([VCMIm][TFSI]) to 2-hydroxyethyl acrylate monomer (HEA) as 1:2, the preparation of block-structured conductive polymer by RAFT copolymerization is as follows:

[0083] Under a nitrogen atmosphere, [VCMIm][TFSI] monomer (2.6165 g, 6 mmol) was dissolved in a 10 mL toluene solution to obtain a monomer solution; a mixed solution of BSTP (0.5% of the total mass fraction of the two monomers) and AIBN (1% of the total mass fraction of the two monomers) dissolved in 5 mL toluene was added to the above monomer solution, and polymerized at 70°C for 12 to 24 hours. After the polymerization, HEA monomer (1.3934 g, 12 mmol) was added continuously, and the polymerization was continued for 12 to 24 hours. After the polymerization, it was purified and dried to obtain a block-structured polyionic liquid-based cross-linked network conductive copolymer.

[0084] Example 21 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0085] The method is the same as Example 20, except that the molar ratio of [VCMIm][TFSI] monomer to HEA monomer is replaced with 1:10, and the amounts of BSTP and AIBN are adjusted accordingly.

[0086] Example 22 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0087] The method is the same as Example 20, except that the molar ratio of [VCMIm][TFSI] monomer to HEA monomer is replaced with 1:50, and the amounts of BSTP and AIBN are adjusted accordingly.

[0088] Example 23 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0089] The method is the same as Example 20, except that the molar ratio of [VCMIm][TFSI] monomer to HEA monomer is replaced with 1:100, and the amounts of BSTP and AIBN are adjusted accordingly.

[0090] Example 24 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0091] The method is the same as Example 20, except that the HEA monomer is replaced by the HPA monomer, and the amounts of BSTP and AIBN are adjusted accordingly.

[0092] Example 25 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0093] The method is the same as Example 21, except that the HEA monomer is replaced by the HPA monomer, and the amounts of BSTP and AIBN are adjusted accordingly.

[0094] Example 26 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0095] The method is the same as Example 22, except that the HEA monomer is replaced by the HPA monomer, and the amounts of BSTP and AIBN are adjusted accordingly.

[0096] Example 27 Preparation of polyionic liquid-based cross-linked network conductive copolymer

[0097] The method is the same as Example 23, except that the HEA monomer is replaced by the HPA monomer, and the amounts of BSTP and AIBN are adjusted accordingly.

[0098] Example 28 Application of polyionic liquid-based cross-linked network conductive copolymer as a binder in the preparation of carbon-based composite bipolar plates

[0099] In Examples 1 to 4, conductive copolymers with different molar ratios were prepared by photoinitiated polymerization. Different molar ratios lead to different microscopic compositions in the polymers, which in turn have a great influence on the material properties.

[0100] 1) Conductive material pretreatment: The carbon nanotubes were placed in a beaker and manually stirred for 10 min using a glass rod, then transferred to a mortar and manually ground for 10 min to prepare a conductive skeleton material;

[0101] 2) The conductive skeleton material is placed in a mortar and mixed with conductive polymers in different molar ratios to obtain a uniform mixture. The mixture is placed on a flexible graphite paper and placed in a hot press for hot pressing at a pressure of 3 MPa and a temperature of 150°C. The heater is then turned off and cooled to room temperature at a pressure of 3 MPa. The pressure is then released to obtain a carbon-based composite bipolar plate (the content of the conductive skeleton material in the carbon-based composite bipolar plate is 15wt.% to 30wt.%).

[0102] The effects of different molar ratios on the conductivity and bending strength of the composite bipolar plate were investigated, and the specific results are shown in Table 1.

[0103] Table 1 Performance of carbon-based composite bipolar plates when the conductive polymers prepared in Examples 1-4 are used as binders

[0104] sample <![CDATA[Conductivity σ / S cm -1 > Bending strength / MPa Example 1 138 56 Example 2 113 38 Example 3 92 21 Example 4 81 19

Claims

1. New conductive polymer with high mechanical strength and high toughness, It is characterized in that The conductive polymer is a polyionic liquid-based cross-linked network conductive copolymer obtained by copolymerizing carboxyl-functionalized imidazole ionic liquid monomers and hydroxyl-functionalized acrylate monomers; The chemical structure of the carboxyl functionalized imidazole ionic liquid monomer is shown in (I): Among them, X 1 - For TFSI - , SbF 6 - CF 3 SO 3 - CF 3 COO - 、FSI - 、N(C 2 F 5 SO 2 ) 2 - , CH 3 SO 3 - Any one of the following; n represents the carbon chain length of the ionic liquid monomer, and its value ranges from 1 to 10; The chemical structure of the hydroxyl functionalized acrylate monomer is any one of (II), (III) and (IV):

2. A method for preparing the novel conductive polymer with high mechanical strength and high toughness as claimed in claim 1, It is characterized in that The method is as follows: a carboxyl functionalized imidazole ionic liquid monomer and a hydroxyl functionalized acrylate monomer are copolymerized by a photoinitiated polymerization method to construct a polyionic liquid-based cross-linked network conductive copolymer with a random structure.

3. The preparation method according to claim 2, It is characterized in that The specific steps of the photoinitiated polymerization method are as follows: carboxyl functionalized imidazole ionic liquid monomers and hydroxyl functionalized acrylate monomers are mixed evenly with 1-hydroxycyclohexyl phenyl ketone as a photoinitiator with a total mass fraction of the two monomers being 1%, and placed in a 38×8×1 mm glass mold, and irradiated under a wavelength of 365 nm ultraviolet lamp for 0.5 to 20 minutes for polymerization, and after the polymerization is completed, a random structured polyionic liquid-based cross-linked network conductive copolymer is obtained.

4. A method for preparing the novel conductive polymer with high mechanical strength and high toughness as claimed in claim 1, It is characterized in that The method is as follows: using the reversible addition-fragmentation chain transfer polymerization method, carboxyl functionalized imidazole ionic liquid monomers and hydroxyl functionalized acrylate monomers are copolymerized in the presence of AIBN and RAFT agents, and by regulating the order of monomer addition, a block structure or random structure polyionic liquid-based cross-linked network conductive copolymer is constructed.

5. The preparation method according to claim 4, It is characterized in that The specific steps of the reversible addition-fragmentation chain transfer polymerization method are as follows: in a nitrogen atmosphere, a carboxyl functionalized imidazole ionic liquid monomer and a hydroxyl functionalized acrylate monomer dissolved in toluene are uniformly mixed to obtain a monomer mixed solution; a RAFT agent with a total mass fraction of 0.5% of the two monomers and an AIBN with a total mass fraction of 1% of the two monomers are dissolved in toluene, and the obtained mixed solution is added to the above-mentioned monomer mixed solution, and polymerization is carried out at 70° C. for 12 to 24 hours. After the polymerization is completed, purification and drying are carried out to obtain a polyionic liquid-based cross-linked network conductive copolymer with a random structure.

6. The preparation method according to claim 4, It is characterized in that The specific steps of the reversible addition-fragmentation chain transfer polymerization method are as follows: under a nitrogen atmosphere, dissolving a carboxyl functionalized imidazole ionic liquid monomer in toluene to obtain a monomer solution; dissolving a RAFT agent with a total mass fraction of 0.5% of the two monomers and an AIBN with a total mass fraction of 1% of the two monomers in toluene, adding the obtained mixed solution to the above monomer solution, polymerizing at 70° C. for 12 to 24 hours, then adding a hydroxyl functionalized acrylate monomer, continuing to polymerize for 12 to 24 hours, purifying and drying after the polymerization, and obtaining a block-structured polyionic liquid-based cross-linked network conductive copolymer.

7. The preparation method according to claim 4, It is characterized in that The chemical structure of the RAFT agent is any one of (V), (VI), (VII), (VIII), (IX), and (X):

8. The preparation method according to claim 3, 5 or 6, It is characterized in that The molar ratio of the carboxyl functionalized imidazole ionic liquid monomer to the hydroxyl functionalized acrylate monomer is 1:100 to 100:

1.

9. Use of the novel high mechanical strength and high toughness conductive polymer as claimed in claim 1 as a binder in carbon-based composite bipolar plates.

10. The use according to claim 9, It is characterized in that The method comprises the following steps: 1) Conductive material pretreatment: The conductive material was placed in a beaker and manually stirred with a glass rod for 10 minutes, then transferred to a mortar and manually ground for 10 minutes to prepare a conductive skeleton material; 2) The conductive skeleton material and the new type of high mechanical strength and high toughness conductive polymer as a binder are placed in a mortar and mixed to obtain a uniform mixture, the mixture is placed on a flexible graphite paper, and placed in a hot press for hot pressing at a pressure of 3 MPa and a temperature of 150° C., and then the heater is turned off and kept at a pressure of 3 MPa to cool to room temperature, and the pressure is removed to obtain a carbon-based composite bipolar plate; The conductive material is any one of graphite, graphene, carbon fiber, and carbon nanotubes, or a mixture of two of them.